2016
DOI: 10.3892/ol.2016.4130
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA HOTAIR is a marker for hepatocellular carcinoma progression and tumor recurrence

Abstract: Abstract. The present study aimed to investigate the expression level of HOX transcript antisense RNA (HOTAIR) in hepatocellular carcinoma (HCC) and its association with various clinicopathological characteristics, and to further explore the molecular mechanisms of HOTAIR function in HCC. Quantitative reverse transcription-polymerase chain reaction (RT-PCR) was used to detect the expression level of HOTAIR in 60 paired fresh HCC samples and adjacent normal liver tissue samples. The association between HOTAIR e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
81
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(87 citation statements)
references
References 40 publications
5
81
0
Order By: Relevance
“…In addition, HOTAIR was demonstrated to promote proliferation and reduce apoptosis in pancreatic cancer, colorectal cancer, and HCC (10)(11)(12). Overexpression of HOTAIR was positively associated with poor prognosis, tumor progression and recurrence in HCC (13,14). A recent study reported that HOTAIR also promoted the malignant growth of human liver cancer stem cells (15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, HOTAIR was demonstrated to promote proliferation and reduce apoptosis in pancreatic cancer, colorectal cancer, and HCC (10)(11)(12). Overexpression of HOTAIR was positively associated with poor prognosis, tumor progression and recurrence in HCC (13,14). A recent study reported that HOTAIR also promoted the malignant growth of human liver cancer stem cells (15).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study reported that HOTAIR also promoted the malignant growth of human liver cancer stem cells (15). A number of studies implicated that HOTAIR has important roles in the tumorigenesis of HCC (12)(13)(14)(15) Reverse transcription-quantitative polymerase chain reaction (RT-qPCR). RT-qPCR was performed to determine expression of lncRNA HOTAIR (12), and mRNA expression of ABCB1 (16).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that lncRNA HOX transcript antisense intergenic RNA (HOTAIR) expression is significantly higher in HCC tissues than in adjacent non-cancerous tissues (7). Patients with HCC tumors that overexpress HOTAIR have an increased risk of HCC recurrence following hepatectomy, and there is also a correlation between HOTAIR overexpression and increased risk of lymph node metastasis (8). The overexpression of HOTAIR is an independent prognostic factor for HCC recurrence in liver transplant patients (9).…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] HOTAIR causes the transcriptional suppressing of the HOXD locus on chromosome 2 in trans. 14 It recruits polycomb repressiving complex 2 (PRC2) and regulates the chromosome occupancy of EZH2 (a subunit of PRC2), which causes histone H3 lysine 27 trimethylation of the HOXD locus.…”
Section: 10mentioning
confidence: 99%